Fear memory formation can affect a different memory: fear conditioning affects the extinction, but not retrieval, of conditioned taste aversion (CTA) memory - Joels, Gil; Lamprecht, Raphael (Frontiers in Behavioral Neuroscience, 2014)
The formation of fear memory to a specific stimulus leads to subsequent fearful response to that stimulus. However, it is not known whether the formation of fear memory can affect other memories. We study whether specific fearful experience leading to fear memory affects different memories formation and extinction. We revealed that cued fear conditioning, but not unpaired or naïve training, inhibited the extinction of CTA memory that was formed after fear conditioning training in rats. Fear conditioning had no effect on retrieval of CTA memory but specifically impaired its extinction. Extinguished fear memory, after fear extinction training, had no effect on future CTA memory extinction. Fear conditioning had no effect on CTA memory extinction if CTA memory was formed before fear conditioning. CTA had no effect on fear conditioning memory extinction. We conclude that active cued fear conditioning memory can affect specifically the extinction, but not the formation, of future different memory.